Implementasi Metode Cantol Roudhoh Berbasis Modul Dalam Mengembangkan Kemampuan Membaca Permulaan Anak Usia Dini - Nurlianharkah, Raya; Rahmawati, Ida Yeni; Kristiana, Dian (Jurnal Paedagogy, 2022)
This study aims to describe the Implementation of the Cantol Roudhoh method based on the module on developing early childhood reading skills at PAUD Kuncup Harapan. The method used in this study was a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. This study used source triangulation to make the data valid. The results showed that the Cantol Roudhoh method could affect reading ability in early childhood. It means the Cantol Roudhoh method in education can build children’s excellence in learning to read early and can frame an exciting and fun learning environment.